2012
DOI: 10.1111/j.2042-3306.2012.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on equine uterine fungal isolates and antifungal susceptibility patterns (1999–2011)

Abstract: SummaryReasons for performing study: Knowledge of commonly encountered fungi infecting the mare's reproductive tract and their respective drug susceptibilities should improve treatment efficacy in mares with fungal endometritis. This is particularly important when practitioners need to start empiric treatment before culture results are complete. Objective: To report the spectrum of fungal isolates from uterine samples from mares with reproductive problems and their respective antifungal susceptibilities. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 13 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…Diagnosis is based on the presence of fungal elements and inflammatory cells in endometrial smears. Yeast appears as small, round, single cell, brown to black spores on cytological smears obtained from infected mares, whereas molds have long filamentous hyphae [4,71]. It has suggested that the hyphae are more invasive than yeast and, consequently, more difficult to treat and eliminate.…”
Section: Fungal Endometritismentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis is based on the presence of fungal elements and inflammatory cells in endometrial smears. Yeast appears as small, round, single cell, brown to black spores on cytological smears obtained from infected mares, whereas molds have long filamentous hyphae [4,71]. It has suggested that the hyphae are more invasive than yeast and, consequently, more difficult to treat and eliminate.…”
Section: Fungal Endometritismentioning
confidence: 99%
“…Candida albicans can be present in both yeast and hyphal forms and therefore can penetrate deeper into the endometrium and/or growth intracellularly. However, in endometrial cytology and histology used to diagnose fungal endometritis, fungal elements only are visualized in the lumen of the uterus and not penetrate deeper in the endometrium [71].…”
Section: Fungal Endometritismentioning
confidence: 99%
“…Recent advances in equine reproduction were the focus of several papers in the EVJ supplement. Coutinho da Silva presented on a retrospective study of 102 fungal isolates from 92 uterine samples with antifungal susceptibility patterns over 12 years (1999–2011) . It was observed that yeast isolates (mostly Candida spp.)…”
Section: Reproductionmentioning
confidence: 99%
“…are rarely isolated in conjunction with placentitis or abortion, in agreement with the low incidence of this organism in mare reproductive swabs (Hong et al, 1993a;Whitwell, 1988;Albihn et al, 2003;Rickets, 2011;Beltaire et al, 2012). A recent case description of Candida (Meyerozyma) guilliermondii described changes in the placenta similar to other mycotic placental lesions with a thick, brown, gritty covering of the chorionic surface centred mainly around the cervical star region (Stefanetti et al, 2014).…”
Section: Fungalmentioning
confidence: 73%
“…is one of the most common fungi isolated in many areas of the world (Albihn et al, 2003;Rickets, 2011;Beltaire et al, 2012). This low incidence is reflected in the relatively uncommon association of fungi ( Aspergillus spp., Mucor spp., and Absidia spp.)…”
Section: Fungalmentioning
confidence: 99%